Maxillary bone necrosis following the use of formaldehyde containing paste: Case report - Radović Igor; Davidović Lado; Cicmil Smiljka; Tomić Slavoljub; Ivanović Dragan; Bjelović Ljiljana (Serbian Medical Society - Dental Section, Belgrade, 2020)
Many of medicaments used historically in root canal treatment have been shown to be cytotoxic. Paraformaldehid agents (such as Toxavit and Depulpin) are used to devitalize inflamed pulp when local anesthesia is ineffective. The misuse of pulp devitalizing agents may cause damage to gingiva and alveolar bone. This case report demonstrates complications arising after application of paraformaldehyde containing paste, necrosis of the gingiva and alveolar cortical bone, which resulted in great loss of supporting bone. Surgical intervention was required wherein necrotic bone was removed and bone defect was filled with xenograft of bovine origin. After three months endodontic treatment was performed. After the treatment, the patient's complaints were resolved. The use of paraformaldehyde-based agents during endodontic therapy requires special caution.